Michael Collins [videorecording] - Jordan, Neil.; Woolley, Stephen ([S. l.] Geffen Pictures, 1996)
A story of a man who is a hero whose fighting tactics became a model for other 20th century struggles. A stateman who negotiated Ireland's break with England, a political martyr slain for the great cause he lived and breath.
VHS.
Film editors, J. Patrick Duffner, Tony Lawson, A.C.E.
Liam Neeson as Michael Collins, Aidan Quinn, Stephen Rea, Alan Rickman and Julia Roberts.
Best screenplay in 1992 -- Academy Award and Oscar Award.
Keywords: Collins, Michael -- 1890-1922.; Feature films; Revolutionaries -- Ireland -- Biography; Ireland -- History -- Civil War, 1922-1923 -- Biography